Stem-leaves of Panax as a rich and sustainable source of less-polar ginsenosides: comparison of ginsenosides from Panax ginseng, American ginseng and Panax notoginseng prepared by heating and acid treatment - Zhang, Fengxiang; Tang, Shaojian; Zhao, Lei; Yang, Xiushi; Yao, Yang; Hou, Zhaohua; Xue, Peng (Journal of ginseng research, 2021)
Ginsenosides, which have strong biological activities, can be divided into polar or less-polar ginsenosides. This study evaluated the phytochemical diversity of the saponins in Panax ginseng (PG) root, American ginseng (AG) root, and Panax notoginseng (NG) root; the stem-leaves from Panax ginseng (SPG) root, American ginseng (SAG) root, and Panax notoginseng (SNG) root as well as the saponins obtained following heating and acidification [transformed Panax ginseng (TPG), transformed American ginseng (TAG), transformed Panax notoginseng (TNG), transformed stem-leaves from Panax ginseng (TSPG), transformed stem-leaves from American ginseng (TSAG), and transformed stem-leaves from Panax notoginseng (TSNG)]. The diversity was determined through the simultaneous quantiﬁcation of the 16 major ginsenosides. The content of ginsenosides in NG was found to be higher than those in AG and PG, and the content in SPG was greater than those in SNG and SAG. After transformation, the contents of polar ginsenosides in the raw saponins decreased, and contents of less-polar compounds increased. TNG had the highest levels of ginsenosides, which is consistent with the transformation of ginseng root. The contents of saponins in the stem-leaves were higher than those in the roots. The transformation rate of SNG was higher than those of the other samples, and the loss ratios of total ginsenosides from NG (6%) and SNG (4%) were the lowest among the tested materials. In addition to the conversion temperature, time, and pH, the crude protein content also affects the conversion to rare saponins. The proteins in Panax notoginseng allowed the highest conversion rate. Thus, the industrial preparation of less-polar ginsenosides from SNG is more efficient and cheaper.